2021
DOI: 10.1515/jpem-2021-0508
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three novel pathogenic mutations in cystathionine beta-synthase gene of Pakistani intellectually disabled patients

Abstract: Background Classical homocystinuria (HCU) is an autosomal recessive inborn error of metabolism, which is caused by the cystathionine-β-synthase (CBS: encoded by CBS) deficiency. Symptoms of untreated classical HCU patients include intellectual disability (ID), ectopia lentis and long limbs, along with elevated plasma methionine, and homocysteine. Methods A total of 429 ID patients (age range: 1.6–23 years) were sampled from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In 2021, Wasim M. et al conducted a mutation analysis on 429 patients with an intellectual disability from northern areas of Punjab, Pakistan. Only nine patients were identified with homocystinuria, and none had c.833T>C mutation [ 22 ]. A study on three patients in a Pakistani consanguineous family with symptoms in 2021 confirmed homocystinuria was not detected with c.833T>C mutation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Wasim M. et al conducted a mutation analysis on 429 patients with an intellectual disability from northern areas of Punjab, Pakistan. Only nine patients were identified with homocystinuria, and none had c.833T>C mutation [ 22 ]. A study on three patients in a Pakistani consanguineous family with symptoms in 2021 confirmed homocystinuria was not detected with c.833T>C mutation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several nations are screening different IEMs according to their prevalence in that population [83,84] as presented in Table 3 with three most prevalent groups of disorders. In our country (Pakistan), there is no newborn screening program yet available for the screening of inherited metabolic disorders, hence we are making efforts to establish NBS in our country, [9,42,45,62,[85][86][87][88][89] although scarce data are available on such disorders in Pakistan. [9,62,[85][86][87][88][90][91][92][93][94] On the other hand, reports from Pakistan show that burden of inherited disorders is quite high due to consanguinity, hence there is a dire need to develop a NBS program, which can help to minimize the burden of such disorders from the society especially focus on aminoacidopathies, organic acidemias, and fatty acid oxidation disorders.…”
Section: Efforts To Initiate Nbs Program In Asian and Other Countriesmentioning
confidence: 99%
“…There are different treatment modalities and ongoing research studies concentrating on new treatment options (Table 1) [21,28,37,39,47,[52][53][54][55][56][57][58][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. One of the most important facts in treatment are to hold plasma homocysteine as close as to the normal range [1-8, 21, 23, 24, 26].…”
Section: Current and Novel Therapy Optionsmentioning
confidence: 99%
“…Pyridoxine in its active form PLP is a cofactor of numerous enzymes which play an important role in amino acid, fat and carbohydrate metabolism, among others. The recommended treatment of non-responsive patients is methionine-restrict- Liver transplantation Small population surgically treated with liver transplantation to date; danger of postoperative side effects; one adult patient with primary underlying cancer disease and domino liver Tx [39,[54][55][56] Gene therapy Mutation repair Gene therapy is still in childhood shoes, studies focus on adenovirus-associated gene transfer or mini circle DNA vector in mice are confidential [67][68][69][70]; one-time approach would be desirable [37,[56][57][58]61].…”
Section: Supplemental and Dietetic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation